(3bhGYO GdEKHGJ hGdELQGAGJ aj GdJMce GdEdcJQhfi chSjdI daV efGRYGJ GdJLGQI GdEdcJQhfjI (B: s (3OQGSI ebGQfI Hjf GdbGfhf GdeUQj hGddjHj (B/ s - (3SGej eMeO UGdM Tdhas; (3CSGeI CMeO Thbj GdedjLj (B: s; (3LGeYI GdbGgQIs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI , s, 2017)
(3YGdLJ GdOQGSI eSCdI GdEKHGJ aj fXGe GdJMcje GdEdcJQhfj (B: (3hcjajI SQjGf ELQGAGJ gPG GdfXGe hGdJj JJe ef NdGd GdhSGFd GdEdcJQhfjI (B: (3Ydi GYJHGQ Cf fXGe GdJMcje GdEdcJQhfj ef CfSH hSGFd aV GdfRGYGJ GdeJYdbI HGdJLGQI GdEdcJQhfjI(B: (3hbSeJ GdOQGSI deHMK JegjOj NUU dOQGSI eGgjI GdJLGQI GdEdcJQhfjI (B: (3haUdjjf QFjSjjf (B: (3NUU GdChd efgeG dJhVjM GdebUhO HGdJMcje GdEdcJQhfj (B: (3hKGfjgeG dHjGf GdEKHGJ hMce GdJMcje GdEdcJQhfj (B. (3hNdUJ GdOQGSI Edi Cfg hHGdQZe ef fLGM GdJfXje GdPGJj ddJMcje GdEdcJQhfj aj JfajP GdCMcGe GdUGOQI Yf eQGcR GdJMcje GdEdcJQhfj (B: (3JHbi GdMGLI Edi VQhQI JTQjYGJ GdJMcje hGdEKHGJ HTcd jdGFe JhXja hSGFd GdGJUGd GdMOjKI aj GJaGb GdJMcje hELQGAGJg s
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe bGfhf GdeQGaYGJ GdeOfjI hGdJLGQjI (B2017s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3bGfhf GdeQGaYGJ s; (3GdJLGQI GdEdcJQhfjI s; (3GdJMcje GdEdcJQhfjs; (3GdJhbjY GdEdcJQhfjs; (3GdefGRYGJ GdJLGQjI GdEdcJQhfjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3cdjI GdMbhb s